(untitled) (Global Journal of Science Frontier Research, 2022)
This quantitative research study was conducted to illustrate the relationship between temperature and the holding force of an electromagnet in a changing magnetic field. To answer this question, an electromagnet was connected to the direct current while being heated to different temperatures, so as to observe at what temperature a nut attached to the electromagnet would fall off. The results showed that with an increase in the electromagnet’s temperature a lower attractive force is noted. The results also revealed that this relation is linear. The implications of this study could be used to design more energy efficient electromagnets.